Preventable critical incidents in anaesthesia: a retrospective analysis of two anaesthetic mishaps after inadvertent drug administration - Meena, Shyam Charan; Dulara, Suresh Chandra; Meena, Samta; Tripathi, Archana; Nagar, Jitendra (Journal of Society of Anesthesiologists of Nepal, 2016)
Drug errors in anaesthesia can be life threatening. In this article, we report two such mishaps of wrong drug administration. A 12-year-old boy was unintentionally injected atracurium instead of diclofenac for pain relief. He became apneic and did not respond to verbal commands. His trachea was intubated and he was mechanically ventilated. After 40 minutes of sedation, mechanical ventilation and stable hemodynamics, extubation of trachea was done. Another patient was also accidentally injected atracurium in the operating room to provide post-operative analgesia at the end of the surgery. Both the cases had favourable outcome because of a high degree of suspicion, prompt diagnosis and early intubation; very crucial steps in such scenarios. This article concludes that the labels should be carefully checked before drug administration, for the right drug and adequate dosage at the right time.